Ecotoxicology of silver nanoparticles and their derivatives introduced in soil with or without sewage sludge: A review of effects on microorganisms, plants and animals. (October 2019) - Courtois, Pauline; Rorat, Agnieszka; Lemiere, Sébastien; Guyoneaud, Rémy; Attard, Eléonore; Levard, Clément; Vandenbulcke, Franck
Abstract: Silver nanoparticles (AgNPs) are widely incorporated in many products, partly due to their antimicrobial properties. The subsequent discharge of this form of silver into wastewater leads to an accumulation of silver species (AgNPs and derivatives resulting from their chemical transformation), in sewage sludge. As a result of the land application of sewage sludge for agricultural or remediation purposes, soils are the primary receiver media of silver contamination. Research on the long-term impact of AgNPs on the environment is ongoing, and this paper is the first review that summarizes the existing state of scientific knowledge on the potential impact of silver species introduced into the soil via sewage sludge, from microorganisms to earthworms and plants. Silver species can easily enter cells through biological membranes and affect the physiology of organisms, resulting in toxic effects. In soils, exposure to AgNPs may change microbial biomass and diversity, decrease plant growth and inhibit soil invertebrate reproduction. Physiological, biochemical and molecular effects have been documented in various soil organisms and microorganisms. Negative effects on organisms of the dominant form of silver in sewage sludge, silver sulfide (Ag2 S), have been observed, although these effects are attenuated compared to the effects of metallic AgNPs. However, silver toxicity is complex to evaluate and much remains unknown about the ecotoxicology of silver species in soils, especially with respect to the possibility of transfer along the trophic chain via accumulation in plant and animal tissues. Critical points related to the hazards associated with the presence of silver species in the environment are described, and important issues concerning the ecotoxicity of sewage sludge applied to soil are discussed to highlight gaps in existing scientific knowledge and essential research directions for improving risk assessment. Graphical abstract: Image 1 Highlights: The use of silver nanoparticles in products leads to accumulation of silver in sewage sludge. Contamination of terrestrial environment related to sewage sludge land spreading. Exposure to silver may affect microorganisms and organisms living in soil. Impact of the silver species introduced into the soil via sewage sludge. Ecotoxicity of silver contained in sewage sludge when applied to soil. Abstract : The terrestrial ecotoxicity of silver nanoparticles is the result of complex interplay between the properties of the silver species and the receiver medium.